An exploration of individual- and population-level impact of the 2-dose HPV vaccination schedule in pre-adolescent girls. Issue 6 (2nd June 2016) - Donken, Robine; Bogaards, Johannes A.; van der Klis, Fiona R. M.; Meijer, Chris J. L. M.; de Melker, Hester E.
ABSTRACT: Since 2014, several countries have implemented a 2-dose schedule for Human papillomavirus (HPV) vaccination. Licensure of the 2-dose schedule was based on non-inferiority results from immunobridging studies, comparing the antibody levels of the 2-dose schedule in young girls to those of the 3-dose schedule in young adults. Since licensure, additional data on antibody levels and other aspects of the immune response and clinical effectiveness have become available. This review will discuss the current outcomes on immunogenicity and effectiveness together with an exploration on the population impact of 2-dose schedules from a cost-effectiveness perspective. The 2-dose schedule has important benefits, such as easier logistics, reduced expenditure, potentially higher acceptance and fewer side effects. Policymakers and registration authorities should consider whether these benefits outweigh the likely differences on individual- and population-level impact between the 2- and 3-dose schedules.